PENGEMBANGAN MATERI PEMBENTUKAN NILAI-NILAI KARAKTER DALAM ASPEK TOLERANSI, PEDULI LINGKUNGAN, DAN PEDULI SOSIAL UNTUK SISWA SMK - Agnesia Jayanti; Elni Yakub; Rosmawati ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract :One of the efforts that individuals care able to live and recognize thecharacters them characters them selves with all the potential that exist and is able todistingorsh a good value and a bad score and can make their choice. So that they cantake necessary action for the improvement of themselves and their environment bylearning the value of character and also studied three aspects of thecharacter(tolerance, care for environment, social care) that can he indepedendently andincrease empathy and concern for the environment. One can say it the character hi hasmanaged to absorb the values and beliefs. Covication people desired, and serve asa amoral in this life. Therefore researchers feel the need to develop a material on theformation of character values in aspects toleranse, care for environment , social care.Which is expected to he used by guidance and counseling teachers to teach theirstudents. There materials were prepared using the methods of research anaddevelopment (R&D).as for the purpose of research is as follows.1)arragement of thematerials on the formation of characters values in aspects toleranse, care forenvironment, and social care necessary for SMK student in terms of clarity, systematic,image support freshness completeness of the materials and support for the materialsand support for imagges or video and games.2)know the quality of the materialproduced. This material consist of understanding the character, the values of characterprincipples the factors that influence the formation of character tolerance, care forenvironment, social care. The result of the development of these materials shows thequality of the materials which is derived in the categori “Good”.with the acquisition ofthe skor is 4.24 for all aspects of assessment.Keywords: Character, Environment Care and Social Care.